Atypical Autoimmune Encephalitis With Neuropil Antibodies Against a Yet Unknown Epitope - Edwin Thanarajah, Sharmili; Prüss, Harald; Warnke, Clemens; Barbe, Michael T.; Schroeter, Michael; Fink, Gereon R.; Onur, Oezguer A. (Frontiers in Neurology, 2019)
Autoimmune encephalitis often causes acute psychiatric symptoms and epileptic seizures. However, it is becoming increasingly clear that depending on the target antigen both symptoms and disease severity may vary. Furthermore, the identification and characterization of antibody subtypes are highly relevant for personalizing the treatment and to prevent relapses. Here we present an atypical case of encephalitis with cerebellar and temporal dysfunction but without seizures associated with high levels of cerebrospinal fluid neuropil antibodies against a yet unknown epitope on the neuronal surface in the cerebellum, hippocampus, thalamus, and the olfactory bulb. We treated the patient successfully with corticosteoroids, plasmapheresis, and rituximab.